Effectiveness of Diabetes Self-Management Education (DSME) and Family Support in Preventing Diabetic Foot Ulcers - Diana Dayaningsih; Margiyati Margiyati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: Diabetes Mellitus is a chronic disease that requires comprehensive management involving both patients and their families. Diabetes Self-Management Education (DSME) is a crucial strategy for empowering patients and preventing complications, particularly diabetic foot ulcers. This study aimed to evaluate the effectiveness of DSME, combined with family support, in preventing diabetic foot ulcers. Methods: A quasi-experimental, one-group pre- and post-test design was employed. Participants were recruited using purposive sampling. The study included 11 respondents with type 2 diabetes mellitus who were over 40 years old, lived with family, had no significant sensory impairments, could communicate effectively, and were willing to participate. The intervention consisted of three DSME sessions delivered over 14 days at the Sekaran Health Centre. Results: Before the intervention (pre-test), 81.8% of participants demonstrated poor self-care behaviour, while 18.2% exhibited good self-care behaviour. Following the intervention (post-test), there was a significant improvement, with 72.7% demonstrating good self-care behaviour and 27.3% exhibiting poor self-care behaviour. Statistical analysis revealed a significant effect of the DSME and family support intervention on self-care behaviour (p = 0.001; α = 0.05). Conclusion: DSME, combined with family support, is effective in improving self-care behaviour among individuals with type 2 diabetes mellitus, which can contribute to the prevention of diabetic foot ulcers. These findings underscore the importance of integrating DSME and family support into diabetes management programs